Science Education: Issues, Approaches and Challenges (Journal of Education and Educational Development, 2020)
In today’s global education system, science education is much more than fact-based knowledge. Science education becomes meaningless and incomprehensible for learners, if the learners are unable to relate it with their lives. It is thus recommended that Pakistan, like many other countries worldwide should adopt Science Technology Society (STS) approach for delivery of science education. The purpose of the STS approach lies in developing scientifically literate citizens who can make conscious decisions about the socio-scientific issues that impact their lives. The challenges in adopting this approach for Pakistan lie in four areas that will completely need to be revamped according to STS approach. These areas include: the examination system; science textbooks; science teacher education programs; and available resources and school facilities.